Spinal Cord Stimulation as Treatment for Cancer and Chemotherapy-Induced Pain - Sheldon, Breanna L.; Bao, Jonathan; Khazen, Olga; Pilitsis, Julie G. (Frontiers in Pain Research, 2021)
Neuropathic pain is a rampant disease exacting a significant toll on patients, providers, and health care systems around the globe. Neuromodulation has been successfully employed to treat many indications including failed back surgery syndrome (FBSS), complex regional pain syndrome (CRPS), phantom limb pain (PLP), radiculopathies, and intractable pelvic pain, among many others. Recent studies have also demonstrated efficacy for cancer-related pain and chemotherapy induced neuropathy with these techniques. Spinal cord stimulation (SCS) is the most commonly employed technique and involves implantation of percutaneous or paddle leads targeting the dorsal columns of the spinal cord with the goal of disrupting the pain signals traveling to the brain. Tonic, high frequency, and burst waveforms have all been shown to reduce pain and disability in chronic pain patients. Closed-loop SCS systems that automatically adjust stimulation parameters based on feedback (such as evoked compound action potentials) are becoming increasingly used to help ease the burden placed on patients to adjust their programming to their pain and position. Additionally, dorsal root ganglion stimulation (DRGS) is a newer technique that allows for dermatomal coverage especially in patients with pain in up to two dermatomes. Regardless of the technique chosen, neuromodulation has been shown to be cost-effective and efficacious and should be given full consideration in patients with chronic pain conditions.